Edukasi Pasangan Usia Subur tentang KB Intra Uterine Device (IUD) dengan Media Audiovisual - Dewi Andang Prastika; Hanifa Andisetyana Putri; Elisa Ulfiana; Yuli Ayuningsih (Universitas Sebelas Maret, 2024)
According to the World Health Organization (WHO), the purpose of family planning is to avoid unwanted births, regulate pregnancy intervals, control the time of birth, and determine the number of children in the family. There are several contraceptive methods or devices that can be used, including birth control pills, birth control injections, implants, condoms, intrauterine contraceptive devices (IUD) and medical surgery for women (MOW) (Sari, 2019). Contraceptive devices that have high effectiveness in preventing pregnancy are long-term contraceptives or what are called Long-Term Contraceptive Methods (MKJP). Selected Effective Conception Methods (MKET) include IUD, Implant, MOW, and MOP. The method of implementing community service includes the preparation, implementation, and evaluation stages. Community service activities will be carried out in May 2022, in Gringsing sub-district, Batang district. After conducting education using audiovisual media, it turned out that young couples' knowledge about intrauterine contraceptive devices increased by 40%. In conclusion Audio visual media increases knowledge of couples of childbearing age about intrauterine contraceptive devices.